2012
DOI: 10.1002/pc.22388
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of networking waterborne polyurethane/silica nanocomposites by addition of poly(ester amine) dendrimer

Abstract: The second‐generation poly(ester amine) dendrimer was prepared by Michael addition reaction and esterification reaction at first. Then, a series of novel waterborne polyurethane (WPU)‐based composites were prepared by the addition of poly(ester amine) dendrimer into the WPU. The structures and the morphology of the WPU composites were measured with Fourier transform infrared spectrometer, scanning electron microscopy, and X‐ray diffraction. SEM images revealed that the nanosilica was well dispersed in the WPU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The nanocomposites do not break at the tests conditions. Hydrogen bonding interaction among fillers/WPU matrix, as evidenced in FTIR section, can be responsible for this behavior . Unlike the others samples the WPU nanocomposite with 3% w/w of synthetic talc D43001 as filler achieved higher values of Young Modulus and stress/strain when compared to 5 and 10% w/w (Figure S1).…”
Section: Resultsmentioning
confidence: 88%
“…The nanocomposites do not break at the tests conditions. Hydrogen bonding interaction among fillers/WPU matrix, as evidenced in FTIR section, can be responsible for this behavior . Unlike the others samples the WPU nanocomposite with 3% w/w of synthetic talc D43001 as filler achieved higher values of Young Modulus and stress/strain when compared to 5 and 10% w/w (Figure S1).…”
Section: Resultsmentioning
confidence: 88%
“…The peaks at 1718.9 cm −1 (CO stretching vibration), 1128.1 cm −1 (CO symmetric stretching), and 1042.5 cm −1 (asymmetric stretching) were the characteristic absorption bands of polyester. From above analysis, it can be concluded that the different generation hyperbranched polyester were successfully synthesized .…”
Section: Resultsmentioning
confidence: 94%
“…This material caused to a considerable increase in the thermal stability of epoxy resin. Han synthesized a dendrimer binded silica nanosphere based composite with waterborne polyurethane (WPU) to improve the physical properties WPU. G2‐polyester amine dendrimer with divergent strategy was selected to bind to the silica surface through Michael addition and esterification.…”
Section: Silica Spheres For Dendrimer Functionalizingmentioning
confidence: 99%
“…This dendrimer based WPU composite had higher dynamic mechanical and thermal feature than pure WPU. Thermogravimetric analysis showed that this composite had higher stability and glass temperature (Figure ) …”
Section: Silica Spheres For Dendrimer Functionalizingmentioning
confidence: 99%